2016
DOI: 10.1039/c6nr06850b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of the full-length amyloid Aβ42 protein in dimers

Abstract: The self-assembly of amyloid (Aβ) proteins into nano-aggregates is a hallmark of Alzheimer’s disease (AD) development, yet the mechanism of how disordered monomers assemble into aggregates remains elusive. Here, we applied long-time molecular dynamics simulations to fully characterize the assembly of Aβ42 monomers into dimers. Monomers undergo conformational changes during their interaction, but the resulting dimer structures do not resemble those found in fibril structures. To identify natural conformations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 70 publications
9
72
2
Order By: Relevance
“…This in silico study showed the stability of an Aβ1-42 dimer that interacted with a long filament, which is consistent with the in vitro experimental study where fibrils facilitated the nucleation of Aβ1-42 peptides, simultaneously using two monomers in the initial step of oligomer formation [95]. However, Zahng et al reported that the probability that Aβ1-42 dimers exist in a U and S shape is very low [96]. …”
Section: Introductionsupporting
confidence: 82%
“…This in silico study showed the stability of an Aβ1-42 dimer that interacted with a long filament, which is consistent with the in vitro experimental study where fibrils facilitated the nucleation of Aβ1-42 peptides, simultaneously using two monomers in the initial step of oligomer formation [95]. However, Zahng et al reported that the probability that Aβ1-42 dimers exist in a U and S shape is very low [96]. …”
Section: Introductionsupporting
confidence: 82%
“…These values run in contrast with (i) previous OPLS MD simulation starting from multiple conformations with 0.9% of helix and 6.6% of β -strand, 20 (ii) recent standard and accelerated MD trajectories using AMBER99sb-ildn/TIP3P 24 with 4% of helix and 5% of β -strand, 22 vs 6% and 24% with our F99 contents, and (iii) to a lesser extent to extensive DMD simulations of A β 42 peptides coupled to an implicit solvent four-bead CG model with 0% of helix and 15.7% of β -strand. 52 …”
Section: Discussionmentioning
confidence: 72%
“…3 and Supplementary Movie 2 reveal a number of features of the dimer assembly process. First, in contrast to a slow Aβ42 dimer formation in solution 14 , the dimer on the surface assembles rapidly, after ~23 ns of simulation ( Fig. 3a).…”
Section: Resultsmentioning
confidence: 98%
“…Figure 2a shows a few snapshots illustrating the structural change of Aβ monomers induced by its interaction with POPC bilayer. The initial conformation of Aβ monomer (snapshot (i)), taken from our recent paper 14 , has essentially random coiled configuration. However, already after ~ 500 ns, two β-strands appear at the C-and N-termini of the molecule (snapshot (ii)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation